The Mediating Role of Resilience between Self-compassion and Academic Engagement among University Students upon Online Learning - Nurdayana, Wong Fang Kim (Universiti Malaysia Sarawak (UNIMAS), 2022)
This study aimed to investigate the relationship between resilience, self-compassion, and academic engagement among university students in Malaysia. It also investigated gender role and its association with resilience and self-compassion. Research data was collected using an online survey. There were 312 undergraduate students from public and private universities who participated in this quantitative study. The descriptive and inferential statistics were obtained by conducting data analysis using the statistical software, IBM SPSS Statistics 26. The descriptive analysis obtained information on participants’ age, gender, university, faculty, course of study, year of study and latest grade-point Average (GPA), while the inferential analysis conducted Pearson correlation test, Multiple Regression Test and Independent Samples T-test. The analyses revealed that resilience had a significant positive correlation with self-compassion and academic engagement among undergraduate students. The results also showed that self-compassion was a significant predictor mediator between undergraduate students’ resilience and academic engagement. However, the study showed that there was no significant difference in self-compassion and resilience between female and male undergraduate students. This study highlighted the significance of psychological positive constructs, i.e., resilience and self-compassion on enhancing students’ academic performance and readiness to encounter and adapt to daily life obstacles.